Introducing an Etnosemiotic Approach to develop Multimedia Material for Supporting the Alphabetization Process for a Mexican Indigenous Language - Garcia, Ivan (International Journal of Emerging Technologies in Learning (iJET), 2011)
One of the effects of globalization in countriesâ?? education programs is the loss of their native languages. The loss of native languages does not only affect the research work of anthropologists, linguists, and ethnologists; moreover the countryâ??s identity and culture. In this context, our research aims to establish some ethnic contexts which influence studentsâ?? learning and to provide dynamic material to support the learning process in an indigenous language. More specifically, in this paper an etnosemiotic approach is presented to create interactive multimedia material for supporting the alphabetization process in the Zapoteca language in the Mexican Region of Oaxaca. This approach is oriented towards elementary schooling and aims to address some current necessities in indigenous education.